IBM system storage DS8000 architecture and implementation (release 8) - Dufrasne, Bertrand; Brunson, Sherri; Butcher, Andrew; Cook, Jeff; Kimmel, Peter; Stenson, Mike (IBM, International Technical Support Organization, 2016)
This IBM® Redbooks® publication describes the concepts, architecture, and implementation of the IBM DS8880 family. The book provides reference information to assist readers who need to plan for, install, and configure the DS8880 systems. The IBM DS8000® family is a high-performance, high-capacity, highly secure, and resilient series of disk storage systems. The DS8880 family is the latest and most advanced of the DS8000 offerings to date. The high availability, multiplatform support, including the IBM z Systems™, and simplified management tools help provide a cost-effective path to an on-demand world. The new IBM DS8880 family includes two high-performance models (DS8886 Model 981 with its associated DS8886 Expansion Unit Model 98E, and the DS8884 Model 980 with its associated Expansion Unit Model 98B). Two powerful IBM POWER8® processor-based servers manage the cache to streamline disk I/Os, maximizing performance and throughput. These capabilities are further enhanced with the availability of high-performance flash enclosures (HPFEs). A major change with the introduction of the DS8880 is the reduction of the footprint to a 19-inch rack. Like its predecessors, the DS8880 supports advanced disaster recovery (DR) solutions, business continuity solutions, and thin provisioning. All disk drives in the DS8880 storage system include the Full Disk Encryption (FDE) feature. The DS8880 can automatically optimize the use of each storage tier, particularly flash drives and flash cards, through the IBM Easy Tier® feature. The DS8880 also can be integrated in a Lightweight Directory Access Protocol (LDAP) infrastructure.
"Storage.". - "This edition applies to the IBM DS8880 with firmware Release 8.0."--Title page verso. - "SG24-8323-00"--Back cover. - Includes bibliographical references. - Description based on online resource; title from title page (viewed March 28, 2016)
Keywords: Storage area networks (Computer networks); IBM computers; Réseaux de stockage (Informatique); IBM (Ordinateurs)